OC14 : Personalized multichannel transcranial direct current electrical stimulation guided by SEEG in drug-resistant epilepsy: clinical and neurophysiological effects. (March 2022) - Daoud, M.; El Youssef, N.; Salvador, R.; Fierain, A.; Garnier, E.; Wendling, F.; Medina, S.; Benar, C.G.; Ruffini, G.; Bartolomei, F.
Abstract : In refractory epilepsy, transcranial direct electrical stimulation (tDCS) is applied to decrease cortical activity with two (conventional tDCS) or several electrodes (multifocal tDCS). We investigated effects of personalized multisession, SEEG-targeted multifocal tDCS on seizure frequency (SF) and scalp functional connectivity (Fc) as measured by EEG in patients with drug-resistant epilepsy (DRE). Ten patients suffering from DRE were recruited to study therapeutic and neurophysiological effects of long-term multifocal tDCS treatment (Starstim, Neuroelectrics). Therapy consisted of three cycles where each stimulation cycle corresponded to five consecutive days where each patient received 2x20 min tDCS at 2 mA separated by 20 min off. The montages were personalized to target epileptogenic area of each patient as defined by SEEG recordings. SF after the treatment was compared with baseline. Fc changes were analysed using EEG recordings performed before and after each stimulation cycle. After the last tDCS session, 50% of patients (responders) had a SF decrease of 50% or more compared with baseline. We estimated Fc changes between cycles and across responder (R) and non-responder (NR) patients. R presented a decrease in Fc (p<0.05) at the third session in alpha and beta frequency bands compared to the first one. We validated the clinical usefulness of personalized multifocal tDCS targeting epileptic areas identified by SEEG. Moreover, we demonstrated that a decrease in SF is associated to a significant decrease of Fc after three stimulation cycles. Such results suggest that tDCS-induced functional plasticity changes may underlie the clinical outcome differences between R and NR.